1987
DOI: 10.1083/jcb.105.6.2745
|View full text |Cite
|
Sign up to set email alerts
|

Two G-proteins act in series to control stimulus-secretion coupling in mast cells: use of neomycin to distinguish between G-proteins controlling polyphosphoinositide phosphodiesterase and exocytosis.

Abstract: Abstract. Provision of GTP (or other nucleotidescapable of acting as ligands for activation of G-proteins) together with Ca 2+ (at micromolar concentrations) is both necessary and sufficient to stimulate exocytotic secretion from mast cells permeabilized with streptolysin-O. GTP and its analogues, through their interactions with Gp, also activate polyphosphoinositide-phosphodiesterase (PPI-pde generating inositol 1,4,5-trisphosphate and diglyceride [DG]). We have used mast cells labeled with [3H]inositol to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(86 citation statements)
references
References 32 publications
2
83
0
1
Order By: Relevance
“…Similar studies with other permeabilized cells, particularly neutrophils [3], HL-60 cells [4] and RINmSF cells [5], in which Ca2'-independent secretion was observed, and with mast cells in which Ca2* was required [6,7], have led Gomperts and colleagues to propose that an unidentified G protein, designated G,, may mediate GTPySinduced exocytosis (reviewed in [S]). Since treatment of rabbit platelets with PMA enhances the ability of GTPyS to stimulate PLD in membrane preparations PMA, phorbol 12-myristate 13-acetate; PA, phosphatidic acid; PEt, phosphatidyl-ethanol; BAPTA, l,f-bis(oaminophenoxy)ethane-N,N,N,N'-tetraacetic acid; PKC, protein kinase C [9], we have suggested that PLD may be the effector of G, in platelets [l].…”
Section: Introductionmentioning
confidence: 82%
“…Similar studies with other permeabilized cells, particularly neutrophils [3], HL-60 cells [4] and RINmSF cells [5], in which Ca2'-independent secretion was observed, and with mast cells in which Ca2* was required [6,7], have led Gomperts and colleagues to propose that an unidentified G protein, designated G,, may mediate GTPySinduced exocytosis (reviewed in [S]). Since treatment of rabbit platelets with PMA enhances the ability of GTPyS to stimulate PLD in membrane preparations PMA, phorbol 12-myristate 13-acetate; PA, phosphatidic acid; PEt, phosphatidyl-ethanol; BAPTA, l,f-bis(oaminophenoxy)ethane-N,N,N,N'-tetraacetic acid; PKC, protein kinase C [9], we have suggested that PLD may be the effector of G, in platelets [l].…”
Section: Introductionmentioning
confidence: 82%
“…We have previously shown that in the absence of MgATP, the polyphosphoinositide levels drop significantly and re-addition of MgATP at millimolar concentrations restores these levels [28]. The enhancement with MgATP when ARF-regulated PLD is examined in its natural environment may reflect the increased availability of PIP,.…”
Section: Amentioning
confidence: 99%
“…Mast cells were obtained and purified exactly as described previously [5]. The protocol for cytosol depletion was identical to that used for RBL-2H3 cells described above.…”
Section: Studies With Rat Peritoneal Mast Cellsmentioning
confidence: 99%
“…Studies of exocytosis from cells of haematopoietic origin, including mast cells, have indicated an essential role for a Gprotein (G E ) in addition to increases in Ca# + [4,5]. Subsequent work has revealed several candidate G-proteins that are involved in exocytosis.…”
Section: Introductionmentioning
confidence: 99%